The effects of merging student emotion recognition with learning management systems on learners' motivation and academic achievements - Ozek, Muzeyyen Bulut (Wiley, 2018)
Technology diverts engineering education into learning management system for distance education activities. Learning management system facilitates the management of education and training process, including instructor-student, student-student, and student-content communication. Nevertheless, distance education has some disadvantages of not being able to establish active communication with students as in traditional education. This research offers a system which merges student emotion recognition with learning management system. This study aims to investigate the effects of merging student emotion recognition with learning management systems on learners' motivation and academic achievements. In this research, the quasi-experimental design adopted 103 engineering students who were divided into three groups: the control group (participates in face-to-face education), the experimental group I (uses a system that merges emotion recognition with learning management system), and the experimental group II (uses learning management system). As a result of the research, it was found that the academic achievement and motivation of the experimental group I was significantly better than performance of the experimental II and the control group.
Keywords: achievement; distance engineering education; emotion recognition; learning management system; motivation